2014
DOI: 10.1007/s11046-014-9753-5
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan

Abstract: A prospective, cross-sectional study was conducted at a medical center in central Taiwan to understand the prevalence, associated factors, and microbiologic features for oropharyngeal yeast colonization in human immunodeficiency virus-infected outpatients. Oral yeast colonization was detected in 127 (45 %) patients, including 21 (16.5 %) colonized by more than one species. Of the 154 isolates, Candida albicans was the most common species (114, 74 %), followed by Candida dubliniensis (10, 6.5 %), Candida glabra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Nevertheless, oral colonisation of HIV-infected patients in conjunction to low counts of CD4 cells are strong premises for subsequent development of OPC (Fong et al, 1997 (Lin et al, 2013;Drozdowska and Drzewoski, 2008;Binolfi et al, 2005). Regarding C. albicans proportion within the HIV isolates, values similar to the one in this study (70%) have been reported for Taiwan (Ho et al, 2014), Cameroun (dos Santos Abrantes et al, 2014), USA (Merenstein et al, 2013), Spain (Ramírez et al, 2006) or Turkey (Erköse and Erturan, 2007). Percentages can go as high as 90% in India (Maurya et al, 2013), Italy (Giammanco et al, 2002) or UK (Cartledge et al, 1999), 83% in South Africa (dos Santos Abrantes et al, 2014), 79% in Serbia (Mitrovic et al, 1996), or can go as low as 62% in Turkey (Erköse and Erturan, 2007) or Brazil (Costa et al, 2006).…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Isupporting
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, oral colonisation of HIV-infected patients in conjunction to low counts of CD4 cells are strong premises for subsequent development of OPC (Fong et al, 1997 (Lin et al, 2013;Drozdowska and Drzewoski, 2008;Binolfi et al, 2005). Regarding C. albicans proportion within the HIV isolates, values similar to the one in this study (70%) have been reported for Taiwan (Ho et al, 2014), Cameroun (dos Santos Abrantes et al, 2014), USA (Merenstein et al, 2013), Spain (Ramírez et al, 2006) or Turkey (Erköse and Erturan, 2007). Percentages can go as high as 90% in India (Maurya et al, 2013), Italy (Giammanco et al, 2002) or UK (Cartledge et al, 1999), 83% in South Africa (dos Santos Abrantes et al, 2014), 79% in Serbia (Mitrovic et al, 1996), or can go as low as 62% in Turkey (Erköse and Erturan, 2007) or Brazil (Costa et al, 2006).…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Isupporting
confidence: 87%
“…All the Romanian isolates were susceptible to VOR, a situation similar to that in Taiwan (Ho et al, 2014).…”
Section: T H I S C O P Y I S F O R P E R S O N a L U S E O N L Y -D Imentioning
confidence: 57%
See 1 more Smart Citation
“…First, C. dubliniensis is more often recovered from oropharyngeal samples (11). Second, C. dubliniensis is isolated in a majority of cases in combination with C. albicans (65)(66)(67)(68), which could explain why opaque cells of C. albicans are more stimulatory than opaque cells of C. dubliniensis in the growth of a C. dubliniensis biofilm. This evolutionary puzzle, therefore, warrants further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…In Taiwan, the number of HIV-infected patients receiving highly active antiretroviral therapy (HAART) with a favorable CD4 count and suppressed viral load has increased in the recent decade due to the availability of free HAART and implementation of a case management program [8]. Since 1999, the authors have examined the prevalence of and risk factors for oral Candida colonization among HIV-infected outpatients at three hospitals during 2009–2010 in three studies [911]. …”
Section: Introductionmentioning
confidence: 99%